EVALUASI KINERJA SISTEM INFORMASI RUMAH SAKIT JUWITA MENGGUNAKAN FRAMEWORK COBIT 5.0 (STUDI KASUS: RUMAH SAKIT JUWITA) - Maghreza Surya Putra, (2021)
Hospital is a health service institution that provides health services to individuals who really need health services in the form of inpatient, outpatient and emergency services. Juwita Hospital is a private hospital. Juwita Hospital has a desire to continue to improve its services to the community and also improve internal performance, especially in the field of Hospital Information Systems at Juwita Hospital. One way to improve services and internal performance is by measuring IT governance using the COBIT 5.0 method. in this case, the researcher uses measurements with the domains Align, Plan, and Organize (APO), Build, Acquire, Implement (BAI), Monitor, Evaluate And Assess (MEA), and Evaluate, Direct and Monitor (EDM). Then this research will produce a recommendation and also the results of the assessment and also the target to be aimed at or achieved using the Capability Level of this study is Level 3 (three). From the results of the evaluation and measurement, the results of the recommendations and assessment in this study are APO01 at level 1, APO02 at level 1, BAI05 at level 1, MEA01 at level 1, MEA02 at level 2, EDM01 at level 1, EDM04 at level 1. The overall capability level is at level 1, therefore the recommendation that can be given is to carry out further development to be able to achieve the desired Capability Level, namely level 3.